A classroom‐based simulation‐centric approach to microelectronics education. Issue 4 (28th June 2018) - Dickerson, Samuel J.; Clark, Renee M.
Abstract: Introductory courses in microelectronic circuits are integral components to electrical and computer engineering undergraduate curriculums. The nature of the material is well‐suited for the incorporation of simulation tools to enhance student understanding of core concepts. SPICE is an electrical circuit simulation tool that has been widely adopted for industrial applications and education. In many instances, engineering instructors have used SPICE‐based simulation tools for homework problems, laboratory exercises, and course projects. Although generally accepted as beneficial to electronics education, the use of SPICE simulation tools is typically restricted to these types of assignments and not heavily used for classroom activity. In this paper, we present a novel method for incorporating SPICE simulation tools into the classroom. Specifically, in a summer 2017 microelectronics course, we used simulation tools for all aspects of the course, incorporating simulation into lecture, in‐class active learning, as well as assignments, and projects. To evaluate this approach, we carried out a rigorous, comprehensive study of this pedagogical approach on student learning, and perspectives using a variety of direct and indirect assessment methods. The results across all measures showed substantial benefits for students to using this methodology and positive responses to the active learning. Beyond microelectronics and other electrical and computer engineering courses, this approach can be applied to other STEM courses where complex systems are studied and simulation tools for these systems are readily accessible to students.